HUBUNGAN TINGKAT KECEMASAN DENGAN PEMILIHAN KB IUD DI DESA BANYUPUTIH LOR KECAMATAN RANDUAGUNG KABUPATEN LUMAJANG - Faizah, Nur; Ekasari, Tutik; Zakiyyah, Muthmainnah (NHM PRESS, 2023)
One of the factors that influence the choice of IUD contraception is the anxiety factor about side effects it can affect acceptor behavior. The purpose of this study was to analyze the relationship between anxiety levels and the selection of IUD contraseptives in Banyuputih Lor village, Randuagung, Lumajang. The research method used correlation analysis with the approach cross sectional. The population of all postpartum mothers in the village of Banyuputih Lor, Randuagung, Lumajang in April - May 2023 was 25 people. Respondents were taken by total sampling technique, the test used is Chi- Square. The results showed that nearly half of the respondents with moderate anxiety a total of 12 people (48%) did not choose to use IUD KB. The results of the analysis using SPSS were obtained with p value = 0.012 < α = 0.05. There is a correlation between the level of anxiety and the choice of IUD contraseptive in Banyuputih Lor village, Randuagung, Lumajang. It is hoped that midwives have a role in family planning education/counseling, can raise public awareness for family planning, and reduce people's anxiety about choosing IUD contraceptive.